Modeling Audit Trail Management Systems for Real-Time Decision Support in Infrastructure Operations - Ebimor Yinka Gbabo; Odira Kingsley Okenwa; Possible Emeka Chima (International Journal of Scientific Research in Humanities and Social Sciences, 2024)
This paper presents a comprehensive modeling framework for audit trail management systems designed to enhance real-time decision support in infrastructure operations. As modern infrastructures grow increasingly complex and interconnected, the ability to capture, secure, and analyze audit data in real time becomes critical for maintaining operational integrity, compliance, and resilience. The study delineates the core components of audit trail systems, emphasizing secure event capture, tamper-resistant storage, and efficient data retrieval mechanisms. It further explores the integration of audit trails with real-time decision support architectures, enabling proactive operational oversight and rapid response to emerging risks. Key design considerations—including system requirements, security and compliance challenges, and scalability factors—are analyzed to inform robust and adaptable solutions suited to dynamic infrastructure environments. The paper concludes by highlighting future research directions focused on leveraging emerging technologies and adaptive analytics to advance audit trail capabilities further. Overall, this work provides a foundational structure to guide the development of intelligent, secure, and scalable audit trail systems essential for modern infrastructure management.